A framework for the evaluation of InsurTech. Issue 4 (30th December 2020) - Xu, Xian; Zweifel, Peter
Abstract: In recent years, the insurance industry has known rapid development and application of new technologies, leading to the emergence of a large number of innovative products. This constitutes a challenge for stakeholders ranging from consumers, management, investors, and on to regulators, who need to evaluate these so‐called InsurTech innovations. This study applies a modified Delphi method in combination with the Analytical Hierarchy Process of Saaty to first provide the weightings of 42 individual indicators for aggregation to 9 subdimensions, among which degree of innovation, size of potential user base, and delivery of services turn out to be the most important. These subdimensions are in turn aggregated into three main dimensions, (i) management and operations, (ii) level of technology, and (iii) user experience, which are found to have equal weight. In conclusion, this paper proposes a transparent way of evaluating InsurTech innovations that also may provide guidance for their future development.